Batas Aurat Muslimah dalam Pandangan al-Albaniy - Riri Fitria (TSAQAFAH, 2012)
This research is destined to view the perspective of al-Albaniy concerning the boundaries of muslimah’ s aurat. The matter of this research is focused on his views towards the quality of sanad and matn also the understanding of Asma’s hadits,as the hadits which has been the basic argument to determine that problem. Among the factors that became the background of this research is the difference of al-Albaniy compared to the other scholars in judging the quality of Asma’ s hadith. The majority of scholars regards this hadits as  da‘if, while al-Albany considers this hadits potential as a hujjah. The data used in this research is Asma’ s hadith with many ways of advocation along with 13 hadits and 16 atsars. These datas were analized using takhrij al-hadits and fiqh al-hadits method. This research recovers that Asma’s hadith can be used as a reason, this is because it’s irsal also has fulfilled the criteria as a mursal hadits which is competent to become an argument. Further, the matnof Asma’s hadits has fulfilled all the criteria formulated by al-Adlabiy. The validity of Asma’s hadits as an evidence implicates the obligation towards mature muslimahs to cover their aurats other than the face and hands.